(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article discusses the adoption of the Constitution of the Republic of Uzbekistan, its refinement over the years, its historical significance, the enforcement of its provisions, and the enactment of laws and decisions based on it. Particular focus is given to the adoption of the new Constitution through a referendum and its entry into force.